2020
DOI: 10.1016/j.schres.2019.12.021
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of youth with reported family history of psychosis spectrum symptoms in the Philadelphia Neurodevelopmental Cohort

Abstract: Little is known about the impact of family history of psychosis on youth from community samples. To fill this gap, we compared youth with a first-degree relative with psychosis spectrum symptoms (i.e. family history of psychosis spectrum symptoms, FHPS) to youth without FHPS in a cross-sectional analysis of the Philadelphia Neurodevelopmental Cohort (PNC). The PNC is a racially diverse community sample of 9,498 youth ages 8-21 years, of whom 8,928 completed the Family Interview for Genetic Studies to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 74 publications
(85 reference statements)
0
11
0
Order By: Relevance
“…94 More studies have focused on the association between adult and childhood traits, investigating similar or different symptoms across development as well as disorder trajectories (Table 2, Tables S6 and S7, available online). Associations were reported between PRSs of adult traits including schizophrenia, MDD, obsessive-compulsive disorder (OCD), anxiety, and externalizing disorder and clinical and continuous measures of the same/similar trait in childhood and adolescence 48,50,64,66,67,69−74,95−98 or in those at high risk, 99,100 although this was not always the case. 60,68,73,75,95,101−105 An exception is bipolar disorder, for which no significant associations with similar childhood traits, such as mania, were identified.…”
Section: Genetic Factors Explaining Stability In Traits or Associations With Adult Traitsmentioning
confidence: 99%
“…94 More studies have focused on the association between adult and childhood traits, investigating similar or different symptoms across development as well as disorder trajectories (Table 2, Tables S6 and S7, available online). Associations were reported between PRSs of adult traits including schizophrenia, MDD, obsessive-compulsive disorder (OCD), anxiety, and externalizing disorder and clinical and continuous measures of the same/similar trait in childhood and adolescence 48,50,64,66,67,69−74,95−98 or in those at high risk, 99,100 although this was not always the case. 60,68,73,75,95,101−105 An exception is bipolar disorder, for which no significant associations with similar childhood traits, such as mania, were identified.…”
Section: Genetic Factors Explaining Stability In Traits or Associations With Adult Traitsmentioning
confidence: 99%
“…A variety of NLP techniques have been used to characterize different language phenotypes in psychosis with varying degrees of success, mostly focusing on SSD 8 . Here, “schizophrenia spectrum disorders” (SSD) refers to threshold-level primary psychotic disorders 9 , 10 . Elvevåg et al 11 first applied Latent Semantic Analysis to quantify decreased coherence in SSD speech and was able to predict human ratings of organizational structure, tangentiality, and content, as well as discriminating between SSD and control participants with 80–82% accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings provide evidence that familial loading for psychosis, most likely reflecting an increased genetic predisposition [61,62], individually or jointly with an environmental component such as parental socioeconomic background may moderate premorbid functioning among individuals who will later develop a psychotic disorder. Family-based studies have previously reported adjustment difficulties in relatives of psychotic patients, suggesting the involvement of presumed genetic influences [6,18,34,36].…”
Section: Discussionmentioning
confidence: 71%
“…Cases reporting that a first or second degree relative was diagnosed with affective or nonaffective psychotic disorder were marked as having positive FHP (details in supplementary text). Positive FHP has been considered a proxy phenotype for increased genetic risk of psychosis [46,47], supported by molecular genetic evidence demonstrating that individuals with positive FHP are characterized by higher polygenic loading for SZ [61,62].…”
Section: Family Historymentioning
confidence: 99%